ANALISIS KEPEMIMPINAN DALAM PENGELOLAAN WISATA GOA PINDUL: STUDI KASUS PEMANDU WISATA LOKAL - Destiana Nurhasna Ramadhanti, Nurzakkiya Rahma, Vanya Medyana Puspita, Ayura Fatwa Febrianti, (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2024)
Goa Pindul is a subterranean river tourism site spanning 350 meters, situated in the village of Bejiharjo, Gunungkidul. Accessing this tourist destination requires approximately one hour from the center of Yogyakarta City. Established in 2010, this attraction continues to maintain its popularity, with thousands of visitors per day embarking on tours of Goa Pindul. As a tourist site featuring water depths of up to 7 meters, the effectiveness and role of local tour guides accompanying visitors in Goa Pindul merit investigation. Therefore, this study employs a qualitative descriptive research method as a means to uncover the social facts and dynamics occurring in Goa Pindul. Based on the conducted research, social leadership emerges as a crucial skill for tour guides, ensuring they effectively accompany and guarantee the safety of tourists exploring Goa Pindul. The findings underscore the significance of social leadership in navigating the unique challenges presented by the subterranean environment, emphasizing the pivotal role played by guides in enhancing the overall visitor experience. This study contributes valuable insights into the social dynamics of tourist experiences in underground river destinations, shedding light on the importance of leadership skills in ensuring a safe and enjoyable exploration of Goa Pindul.